Starea, urea and soybean meal compared in wintering rations for cows on bluestem pasture - Tucker, L.; Harbers, L.H.; Smith, E.F. (Kansas State University. Agricultural Experiment Station, 2011)
More urea, a torn of nonprotein nitrogen, would be fed to ruminants except for inefficient conversion of urea-nitrogen to Microbial protein, toxicity, lack of palatability and urea segregating in mixed rations. As a supplement for cattle on high-roughage rations, urea should be fed with a readily available energy source for urea nitrogen to be converted to microbial protein by rumen microorganisms. Attempting to overcome some or all of those problems, Bartley and co-workers at Kansas State University (Feedstuffs. 27 Apr. 68; 40:9) developed an expansion-processed mixture of grain and urea (Starea).We tested Starea and soybean meal as protein supplements for beef cows grazing dry bluestem pasture during the winter.
Keywords: Beef; Starea; Urea; Soybean meal; Bluestem pasture